A república democrática de Celso Furtado : o sentido político da sua economia do desenvolvimento - Rafael Pacheco Mourão (2022)
The present thesis proposes a new interpretative perspective for the thought of Celso Furtado. We understand that his economy must be understood from his political language, that is, Celso Furtado's thought can only be understood reliably and in all its transforming power if interpreted from his political meaning. Above all, because it is the political sense of Celso Furtado's thought that allows the development of democratic conditions within a republican order to overcome underdevelopment. And when we focus the interpretation of his thought in the political sense as an organizing element of Furtadian's work, we inscribe his thought in the tradition of democratic republicanism. In this sense, we take the work of Celso Furtado as an expression of the tradition of democratic republicanism to demonstrate the coherence and power of a transformative development project that is anchored in the construction of a “Political economy of the public”.